HPV Vaccination Knowledge and Decision‐Making Among Adults 27 to 45 Years: A Large Online Survey - Matthew E. Lin; Oluwatobiloba Ayo‐Ajibola; Jun Yun; Tyler J. Gallagher; Carlos X. Castellanos; Jonathan D. West; Ian Kim; Sophia Chen; Niels C. Kokot; Tamara N. Chambers (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objective Understand knowledge and barriers to human papillomavirus (HPV) vaccination among United States (US) adults, comparing adults in the original age cohort of 18–26 years to those in the expanded 27–45‐yearyear‐old cohort. Methods A cross‐sectional survey was administered to US adults recruited through social media. Descriptive statistics characterized the data. Multivariate logistic regression identified factors associated with vaccination. Results Among 1735 respondents, the majority were in the 27–45 age group (936, 53.94%). The 27–45‐year group exhibited more knowledge of HPV's link to head and neck cancer and vaccine protection but expressed less concern about HPV infection (all p < 0.05). Key motivators for the history of vaccination in the 27–45 year cohort included vaccine effectiveness (48.65%) and prior knowledge (42.44%). Self‐vaccination rates were comparable across age groups (18–26: 70.62% vs. 27–45: 68.07%, p = 0.256). Older adults were less likely to vaccinate dependents (68.57% vs. 75.00%, p < 0.001) despite higher interest (p < 0.001). Main barriers for unvaccinated 27–45 year old adults included scheduling issues, insurance coverage, and lack of concern for HPV infection (all p < 0.05). Among individuals aged 27 to 45, multivariate logistic regression analysis revealed significantly higher odds of vaccination in those from the Western US (compared to Northeast/Midwest) (OR 3.15, 95% CI: [1.84, 5.39]) and personal history of head and neck cancer (3.01, [1.78–5.09]). Conclusion Most respondents understand HPV risks and are vaccinated. Interventions directed towards education about vaccine safety, the hazards of HPV, and improving access may increase vaccination. Level of Evidence IV.